From Adoption to Execution: Challenges and Frameworks for Cloud ERP Implementation-A Systematic Literature Review - Caroline Hornegger; Michael Kohlegger; Christian Ploder (Cloud Computing and Data Science, 2026)
An increasing number of companies are migrating their Enterprise Resource Planning (ERP) systems to the cloud-an area that remains relatively underexplored, as traditional ERP systems were typically deployed on premises. While many organizations already operate other systems in the cloud, ERP systems are particularly critical because they integrate core business processes and manage daily operations, making cloud migration a high-risk transformation that must be carefully planned and executed to ensure business continuity. This study aims to identify the key challenges and implementation frameworks associated with Cloud ERP migration through a Systematic Literature Review (SLR). Studies published between 2015 and 2025 were retrieved from five academic databases, screened using predefined inclusion and quality criteria, and synthesised using Excel and Orange Data Mining software, resulting in a final sample of 58 studies. The results identify 26 distinct challenges-such as data migration, security and privacy concerns, vendor dependence, and resistance to change-and 12 classes of frameworks intended to mitigate these barriers across different organizational and contextual settings. In contrast to prior reviews that primarily catalogue adoption drivers or isolated challenges, this study contributes a structured synthesis that explicitly maps implementation challenge categories to classes of implementation frameworks across different organisational contexts. This integrative perspective reveals systematic coverage gaps in existing frameworks and provides decision-oriented guidance for selecting implementation approaches in practice.